Susceptibility of four Ipomoea genus weed species to the herbicides saflufenacil or flumioxazin - Saul Jorge Pinto de Carvalho; Leonardo Ferreira Nery; Carlos Alberto Borges Madeira; Jeisiane de Fátima Andrade; Jéssica Cursino Presoto (Revista Agrogeoambiental, 2020)
Among weeds commonly found in Brazil that directly interfere on agriculture, those classified in Convolvulaceae Family may be highlighted, particularly Ipomoea L. genus, popularly known as morning glories. Flumioxazin and saflufenacil are herbicide molecules registered to control these weeds. In this context, this work was developed with the objective of evaluating the susceptibility of four Ipomoea genus weed species to the herbicides flumioxazin and saflufenacil. Two similar and independent experiments were performed in 2017, adopting completely randomized blocks and four replicates. Treatments were organized according to an 8x4 factorial scheme, which eight were the rates of each herbicide and four were the weed species of Ipomoea genus (I. hederifolia, I. nil, I. quamoclit and I. triloba). The following rates were adopted to saflufenacil (g ha-1): 0, 1.5, 3.0, 6.1, 12.3, 24.5, 49.0 and 98.0. The rates adopted to flumioxazin were (g ha-1): 0, 3.75, 7.5, 15.0, 30.0, 60.0, 120.0 and 480.0. Ipomoea genus weed species were completely controlled by the herbicides saflufenacil and flumioxazin, which may be considered excellent alternatives to control morning glories. I. triloba and I. nil were identified as the least sensible species to flumioxazin at the rate of 3.75 g ha-1; lower control of I. triloba was also identified with 7.5 g ha-1 of flumioxazin; rates equal to or higher than 15.0 g ha-1 promoted total control of weeds.